A study of the specificities of sequential antisera to variola and monkeypox viruses by radioimmunoassay - Walls, Harriet H. (1980)
The specificities of antisera during development of the humoral antibody response to poxvirus antigens were examined in monkeys injected with chimp-9 whitepox virus or monkeypox virus. Sera were obtained from 3 African green (vervet) monkeys inoculated with chimp-9 whitepox virus, 1 rhesus monkey inoculated with monkeypox virus, and 2 rhesus monkeys inoculated with soluble monkeypox viral antigen. The sequentially obtained sera from each animal were adsorbed with uninfected chicken chorioallantoic membranes (CAM) or vaccinia virus-infected CAM. The adsorbed sera were tested by radioimmunoassay to determine the specificity of the residual antibodies to vaccinia, variola, and monkeypox viruses. The adsorbed sera at different stages of the immune response showed increasing specificity with time after inoculation. Generally, antibodies in sera collected earlier than 21-27 days after immunization could not be identified after adsorption, but late sera could be identified unequivocally.